Analysis Of Nursing Service Quality On Inpatient Satisfaction At Madani General Hospital, Medan - Rustiani, Rustiani; Sitorus, Rotua Sumihar; Br Ginting Munthe, Novita (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Patient satisfaction is one of the important indicators that must be considered in nursing services. Patient satisfaction is the result of patient assessment of nursing services by comparing what is expected with the reality of nursing services received in a hospital. The purpose of the study was to analyze the quality of nursing services on the satisfaction of inpatients at RSU. Madani Medan. The type of research used in this study is quantitative using an observational approach. The research design used is cross-sectional. The population in this study includes inpatients at RSU. Madani Medan in January 2025 to February 2025 as many as 300 people. The number of samples to be studied according to Slovin was 175 people. Data analysis was carried out using univariate, bivariate and multivariate analysis. The statistical tests used were the chi square test and logistic regression. The results of the chi square test showed a significant relationship between Direct Evidence, Reliability, Responsiveness, Assurance and Empathy of nursing services on inpatient satisfaction at RSU. Madani Medan, where the p-value = 0.000. From the results of the multivariate analysis, the most influential variables in this study were the Assurance variable with an OR value of 66.738, and the Empathy variable with an OR value of 22.142. Conclusion of the study; the majority of patients with respondent characteristics aged 27-38 years, female gender, high school education level, housewife occupation. The quality of nursing services Direct Evidence, Reliability, Responsiveness, Assurance and Empathy can be seen from the attitudes of nurses in providing nursing services carried out for the satisfaction of inpatients at RSU. Madani Medan.